Effect of Green Innovation on Corporate Sustainability Through Green Perceived Organizational Support (Study on the Palm Oil Plantation Industry in Kalimantan) - Garingging, Robin Hendra S; Saluy, Ahmad Badawi; Nawangsari, Lenny Christina; Kasmir, Kasmir (Dinasti Publisher, 2024)
This study aims to analyze the effect of green innovation on corporate sustainability through green perceived organizational support in oil palm plantation industry companies in Kalimantan. The method used in this study is a quantitative descriptive method. The population in this study were all employees working in the oil palm plantation industry in Kalimantan. The data analysis model uses Structural Equation Modeling (SEM) with a sample of 238 people. The analysis technique in this study is Partial Least Square (PLS) using the smart PLS program to test the hypothesis. The results showed that green innovation has a positive and significant effect on green perceived organizational support. Green innovation has a positive and significant effect on corporate sustainability. Green perceived organizational support has a positive and significant effect on corporate sustainability. Furthermore, green perceived organizational support can mediate the influence between green innovation and corporate sustainability in oil palm plantation industry companies in Kalimantan.